2006
DOI: 10.1590/s0066-782x2006000300010
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de prevalência e multiplicidade de fatores de risco cardiovascular em hipertensos do Município de Brusque, SC

Abstract: OBJECTIVETo investigate the prevalence and multiplicity of additional risk factors (RF) in a population sample of hypertensive smokers, diagnosed and enrolled at the Hiperdia Program of the Ministry of Health, in the city of Brusque, SC, Brazil. METHODSDetermination of the anthropometrical parameters and laboratory variables recognized as cardiovascular risk factors. RESULTSElevated prevalence of RF in addition to systemic arterial hypertension (SAH) and smoking, confi guring the multiplicity that concurs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
0
4
0
13
Order By: Relevance
“…The excess of body fat remains the most important isolated factor related to BP increase and AH 24 , thus, obesity is one of the main factors responsible for AH and several studies 25,26 have demonstrated the cause-and-effect relationship between body mass increase and BP increase.…”
Section: Discussionmentioning
confidence: 99%
“…The excess of body fat remains the most important isolated factor related to BP increase and AH 24 , thus, obesity is one of the main factors responsible for AH and several studies 25,26 have demonstrated the cause-and-effect relationship between body mass increase and BP increase.…”
Section: Discussionmentioning
confidence: 99%
“…Esses índices podem variar em função da população estudada, mas são semelhantes à prevalência encontrada em outros países da América Latina Em relação aos FR para HAS, grande parcela dos casos apresentava algum FR para DCV como tabagismo (22,84%), sedentarismo (39,31%) ou sobrepeso (32,09%), dados consonantes com a literatura. Em estudo populacional de amostra representativa de hipertensos, mostrou prevalência considerável de sobrepeso e de obesidade 14 . O sedentarismo constitui também, um dos principais fatores de risco para DCV, acometendo entre 50% e 80% da população mundial 15 .…”
Section: Discussionunclassified
“…Assim como em outros estudos como, por exemplo, de Mendonça et al (2004), Rosini et al (2006) e Carolino et al (2008, os dados referentes HAS foram os de maior prevalência (67,2). Sabe-se que a HAS mais prevalente entre os idosos e aumenta sua proporção com o avanço da idade.…”
Section: Discussionunclassified
“…A sua combinação, usualmente, representa um risco total aumentado para doenças cardiovasculares, comparado ao risco resultante da soma de seus efeitos isolados, indicando efeito sinérgico entre eles. Portanto, uma prevenção efetiva das doenças cardiovasculares s ser alcançada com a melhoria global do perfil de risco de indivíduos e populações (ROSINI et al, 2006;MONTENEGRO NETO, 2008). Por isso, a importância de se identificar riscos precocemente na Atenção Básica de Saúde e de se avaliar adequadamente os dados antropométricos da população.…”
Section: Introductionunclassified